Force Analysis and Energy Harvesting for Innovative Multi-functional Shoes - Xu, Borui; Li, Yang (Frontiers in Materials, 2019)
The research of wearable energy harvesting and storage devices has attracted tremendous attention from researchers with commercial wearable devices emerging in the life as new mainstream. Among them, shoes are a better choice for energy harvesting. However, most of the existing energy harvesting and storage shoes have complex structures, poor wearing comfort, and high cost. In order to solve these problems, a kind of innovative multi-functional shoes is developed and discussed in this paper. The shoe contain two main parts. One is a rubber column used as heel material, which plays a role in cushioning and damping during movement and making the shoe more comfortable to wear. The other one is a circuit system designed to realize energy harvesting, energy storage, and emergency charging of electronic products during walking. The performance test of the rubber column is carried out, and then the structure and geometric size of the rubber column is optimized according to its performance, human weight, and gait. Finally, the stress and energy harvesting of the multi-functional shoes in different gait conditions are analyzed. The analysis results show that the developed innovative multi-functional shoe has good stability and versatility when working under different gait, and the rubber column is beneficial to improve the wearing comfort of energy harvesting shoes.